PENGARUH MODEL PEMBELAJARAN COOPERATIVELEARNING TIPE TEAMS GAMES TOURNAMENTS DIINTEGRASIKAN DENGAN MEDIA PUZZLE TERHADAP HASIL BELAJAR IPS SISWA SDN GUGUS II BENGKULU UTARA - Septia Herjanah; Herman Lusa (JURIDIKDAS, 2023)
Learning Models of Teams Games Tournaments Type Integrated with Media Puzzles on student learning outcomes in social studies subjects of class V SDN Gugus II Bengkulu Utara. The type used is quantitative research. The method used is quasy experiment with research design The Matching Only Pretest-Postest Group Design. The population is SDN Gugus IIBengkulu Utara. The sampling technique uses cluster random sampling. The sample is B-accredited SDN and KTSP curriculum. Class V at SDN 090 with the number of students as many as 15 students as the experimental class and class V students at SDN 099 with the number of students as many as 15 students as the control class. The t-test results get tcount (4.132)> t table (1.666). The tcount obtained is higher than ttable, it can be concluded that there is a significant influence of the Cooperative Learning learning model Teams Games Tournaments Type Integrates With Media Puzzle on Social Studies learning outcomes of students in class V SDN Gugus II Bengkulu Utara.